2015
DOI: 10.1016/j.celrep.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneities in Nanog Expression Drive Stable Commitment to Pluripotency in the Mouse Blastocyst

Abstract: Summary The pluripotent epiblast (EPI) is the founder tissue of almost all somatic cells. EPI and primitive endoderm (PrE) progenitors arise from the inner cell mass (ICM) of the blastocyst stage embryo. The EPI lineage is distinctly identified by its expression of pluripotency-associated factors. Many of these factors have been reported to exhibit dynamic fluctuations of expression in embryonic stem cell cultures. Whether these fluctuations correlating with ICM fate choice occur in vivo remains an open questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
141
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(162 citation statements)
references
References 41 publications
16
141
0
Order By: Relevance
“…This was previously suggested by cell lineage tracing experiments (Chazaud et al, 2006;Meilhac et al, 2009) and confirmed by live cell tracking with a Nanog-GFP reporter (Xenopoulos et al, 2015). Interestingly, however, it was shown (Xenopoulos et al, 2015) that a few cells expressing low levels of Nanog-GFP until a relatively late blastocyst stage can strongly upregulate Nanog-GFP expression eventually, which is suggestive of fate reversion. The relative levels of NANOG and GATA6 were not examined in this study and it might be the balance between the two transcription factors that is important rather than their absolute amounts.…”
Section: Tipping the Balance Between Epi And Pe Fatesmentioning
confidence: 82%
See 3 more Smart Citations
“…This was previously suggested by cell lineage tracing experiments (Chazaud et al, 2006;Meilhac et al, 2009) and confirmed by live cell tracking with a Nanog-GFP reporter (Xenopoulos et al, 2015). Interestingly, however, it was shown (Xenopoulos et al, 2015) that a few cells expressing low levels of Nanog-GFP until a relatively late blastocyst stage can strongly upregulate Nanog-GFP expression eventually, which is suggestive of fate reversion. The relative levels of NANOG and GATA6 were not examined in this study and it might be the balance between the two transcription factors that is important rather than their absolute amounts.…”
Section: Tipping the Balance Between Epi And Pe Fatesmentioning
confidence: 82%
“…This gives rise to a mutually exclusive 'salt and pepper' expression pattern of NANOG and GATA6 by embryonic day (E) 3.75. Cell lineage tracing and live cell tracking analyses (Chazaud et al, 2006;Kurimoto et al, 2006;Plusa et al, 2008;Meilhac et al, 2009;Xenopoulos et al, 2015) show that this process occurs in individual ICM cells asynchronously, spanning from ∼E3.0-E3.75 (Gerbe et al, 2008;Plusa et al, 2008;Bessonnard et al, 2014). Therefore, a few cells coexpressing both transcription factors can still be identified at ∼E3.75 in some embryos, and the emergence of NANOG + / GATA6 − EPI cells is currently the first known sign of the specification process.…”
Section: Tipping the Balance Between Epi And Pe Fatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the dynamicity and stochastic molecular heterogeneity, mechanistic understanding of the first lineage specification requires quantitative description of the gene expression dynamics in living embryos during morphogenesis at single-cell resolution [16]. However, to date, only a limited number of fluorescence gene expression reporter mice suitable for live imaging are available [5,[17][18][19], quantitative analysis of gene expression dynamics has begun only recently [19], and it has not been systematically integrated with cell lineage segregation pattern.…”
Section: Introductionmentioning
confidence: 99%